PENGARUH MOTIVASI BELAJAR DAN PENGUASAAN KOSAKATA TERHADAP PEMAHAMAN MEMBACA BAHASA INGGRIS DI SMK BIPTA JATI TAHUN 2022 - Yuli Dwiyanti; Retno Purwani; Ayu Pratiwi (Nusantara Hasana Journal, 2023)
English is a language that is commonly used in various countries as a language of communication between nations or in other words English is used as an international language. In this communication process, there are parties involved, namely communicators and communicants. The results of communication between the communicator and the communicant can be good (fluent) or vice versa. The purpose of this study was to determine the effect of learning motivation and vocabulary mastery on English reading comprehension at Bipta Jati Vocational School in 2022. The research method in this study used Google form. The population in this study was the students of SMK Bipta Jati in 2022 totaling 120. The instrument of this research was a questionnaire. This study used the Chi-Square Test, with p-value 0.009 <0.05. The conclusion is that there is an Influence of Learning Motivation and Vocabulary Mastery on English Reading Comprehension at Bipta Jati Vocational High School in 2022.